Finite difference time domain discretization for room acoustic simulation based on the non-linear Euler equations - Hölter Arne; Weinzierl Stefan; Lemke Mathias (Acta Acustica)
In comparison to geometric acoustics, wave-based simulation techniques in the time domain have a much higher degree of accuracy. Latest modeling techniques like immersed boundaries reduce modeling effort significantly. This paper aims to present and discuss the use of techniques for first-order partial differential (non-linear) Euler equations in finite-difference time-domain simulations for room acoustic applications. This includes the governing equations, spatial and temporal discretization schemes, filtering schemes, and boundary conditions. All methods are fully parallelizable and mostly known from computational aeroacoustics. They are analyzed with respect to their dispersion and stability behavior as well as their computational efficiency. They are proven in a cubic room with rigid boundaries. Finally, a volume penalization method is used to mimic real impedance boundary conditions in benchmark cases for room acoustic simulations to demonstrate the transferability to real-world scenarios.